PENGARUH TURNOVER INTENTION, ORGANIZATION COMMITMENT, DAN LOCUS OF CONTROL TERHADAP DYSFUCNTIONAL AUDIT BEHAVIOUR - Muhammad Yolly Setiawan; Fauziah Aida Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to find out and evaluate the influence of turnover intention, organization commitment and locus of control toward dysfunctional audit behavior. Based on the census method, th is research used samples of 64 respondents as auditors who work in Finance and Development Supervisory Agency (BPKP) of Aceh Representative. This study was conducted using primary data obtained through the questionnaire. The data analysis used multiple regression analysis with data processing using SPSS version 22. The result of the study shows that turnover intention does not have a significant influence on dysfunctional audit behavior. While organization commitment and locus of control have a significant influence on dysfunctional audit behavior.